Response of different plant functional types to environmental variability on Marion Island : quantifying diurnal patterns over a seasonal cycle using the photochemical reflectance index - Zietsman, Alta (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018. ENGLISH ABSTRACT: Marion Island forms part of the Prince Edward Island group, situated near the latitude of 47° South. Seasonal and temporal variability in climate on Marion Island has been described as muted, due to the thermal buffering of the surrounding ocean. This is thought in turn to lead to an extended growing season. However, empirical in situ measurements of net primary production (NPP), are lower than estimations based on annual temperature and precipitation. The aim of this study was to explore which potentially limiting environmental factors exert control over photosynthetic behaviour at a range of sub-annual temporal scales, in order to better understand what limits production in plant functional types (PFTs) typical of Marion Island. The three main PFTs selected for study were lower plants, cushion plants and grasses. Spectral reflectance sensors were used in situ to investigate the diurnal and seasonal patterns of physiological stress and inferred photosynthetic behaviour. The Photochemical Reflectance Index (PRI) is calculated from a ratio of reflected versus incoming light wavebands, that are influenced by a change in carotenoid ratios, indicating photosynthetic efficacy through the activity of the xanthophyll cycle. The xanthophyll cycle is closely linked to photosystem II and thus an important component of the non-photochemical quenching (NPQ) process that acts as a photo-protection mechanism. PRI measurements require careful interpretation in the absence of any independent confirmatory measurements. Repeated ancillary measurements of leaf chlorophyll fluorescence and leaf chlorophyll content via independent instrumentation provided support for the PRI measurements as an indicator of physiological stress. This approach was also used to confirm that the point monitoring of individual canopies was representative of surrounding vegetation. Contrary to the assumption that climate variability is muted, fine temporal scale monitoring revealed ...